(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
COPD is associated with a number of alterations in electrocardiograms (ECGs), including the frontal P-wave axis, which is the most popular and widely recognized, and it involves shifting the P-wave axis verticalization, which is more than +60º, is strongly indicative, is believed to be caused by hyperinflated lungs, and fails to cause lung illnesses that limit airflow.